Forensic Analysis of Time Markers of Digital Recordings - S. M. Petrov (Теория и практика судебной экспертизы, 2021)
The article presents the results of summarizing expert practice on the examination of the features of digital video and sound recordings, which make it possible to determine the time of file creation and date of the recorded events. The author introduces the concept of “time marker” and proposes the classification of time markers in the file name, time attributes, and metadata by form and source of origin. The basic principles of time representation by various file systems are stated. The relationships between different time markers for original records and records made in other ways are analyzed. The article provides examples of using time markers to diagnose the method of making a record.Various types of time markers that are part of the recorded signal are considered. It is shown which of the recorded events can act as time markers. The author also analyses the possibility of dating using astronomical events. Differences between absolute and relative dating are considered concerning the study of audio and video files. Conclusions are drawn about the significance of the study of time markers for diagnosing the method of making a signalogram, performing relative or absolute dating of recorded events, or technological processes of making a signalogram.